Histological Analyses And Detection Of Azadirachtin From In Vitro Cultures Of Sentang (Azadirachta Excelsa (Jack) Jacobs) - Mihiret, Yohannes Adane (2005)
The growth profiles of calli and suspension cultures from leaf segments of in vitro grown Azadirachta excelsa shoots were studied to establish plant regeneration system and to quantitatively detect the presence of azadirachtin in suspension cultures. A highly significant variation (p < 0.01) was observed among the plant growth regulators used in the callogenesis experiments. Explants treated with callus induction media (IM) containing MS medium, Murashige and Skoog's (1962)' supplemented with 9 pM 2'4- Dichlorophenoxy-acetic acid (2'4-D) and 4.4 pM Benzyl Amino Purine (BAP) showed the highest callusing efficiency (94%). But, calli with meristematic features (semifriable to friable texture and pale yellow to yellow color) were obtained from 88% of explants on IM containing MS supplemented with 36.2 pM 2,4-D. Three morphologically different types of calli could' be observed on proliferation media (PM); i.e. friable and pale yellow calli, sometimes with nodules and watery appearance . . . 111 (Type-1); semi friable, nodular, proliferative and pale yellow to white calli (Type-2); and semi-compact calli with heterogeneous appearance (pale beige (brown) at the base with pale and granular areas at the surface) (Type-3). Maximum fresh weight of calli with meristematic features (8.6 g) was obtained using PM containing 2.26 pM 2,4-D and 33.3 pM BAP. Growth rate studies on these calli indicated that a 2-3 weeks subculturing cycle was most suitable. In cell suspension cultures, maximum cell-biomass increase (1.36 + 0.041 g) was obtained in media containing 2.26 pM 2,4-D and 0.22 pM thidiazuron (TDZ) after six weeks of culture incubation (with a weekly subculturing cycle). Nevertheless, growth rate studies indicated that 12-15 days was the end of the exponential growth phase (maximum average settled cell volume (4.5 mL) was attained). Thus, a 12-15 days subculturing cycle is recommended. Cells released into the various suspension media formed fine cell aggregates which further developed to globular like structures, which, upon transfer to growth regulator free media, produced unipolar shoot primordia (visible to the naked eye), with a 63% conversion rate. Histological studies at various stages of calli development clearly showed progressive structural changes of cells (in calli) into meristematic groupings (aggregates), and hence shoot primordia. The study showed marked morphological differences among the different calk Type-1 calli had smaller sized cells appearing in clusters and with prominent nucleus. Type-2 calli had isodiametric, but randomly dispersed groups of dividing cells. Type-3 calli had larger and highly vacuolated internal cells and actively RSWSTAKAAN SULTAN ABMlL SAMAD UIYVER81n m MALAYSIA dividing external cells. Cell aggregates also had low to moderate intercellular polysaccharide contents coupled with asymmetric cell division patterns. Moreover, regenerants from the cell aggregates showed sufficient precambial attachment to the parent tissue suggesting organogenesis (instead of embryogenesis) as regeneration pathway. Azadirachtin was detected and quantified in different cell aggregate samples from suspension cultures, using high performance liquid chromatography (HPLC). Samples varied significantly with regard to the accumulation of qzadirachtin. Moreover, the accumulation of the substance in the samples was dependent on the type of growth regulator used. Hence, 2,4-D (2,4-Di-chlorophenoxy-acetic acid) treated samples showed the highest (0.966 mg/g) azadirachtin content, as compared to NAA (Naphthalene Acetic Acid) treated samples (0.793 mg/g).